Strategi Pengembangan Pemasaran Media Sosial Pada Cafe Gusta And Co - Siti Sabira Azzahra Janah; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Cafe is one of the business places that has increasingly developed in recent years, one of which is Cafe Gusta and Co in Karawang. The aim of this research is to determine the appropriate marketing strategy position in developing the Gusta and Co cafe through social media to survive and compete with other business actors in the current digital era. The method used is a descriptive qualitative approach, using SWOT analysis, IFAS and EFAS analysis, quadrants and SWOT matrix. By conducting interviews with the Gusta and Co cafe manager and 7 consumers to provide assessments on the questionnaire via Google form. The results show that Cafe Gusta and Co is in quadrant II, namely being in a strategic diversification position as a strategy that can be carried out by utilizing its strengths to face threats, such as its location strategy, having a spacious and modern place, good quality and taste, this can be and is maintained for attracting a lot of new consumer interest as well as efforts to increase sales.